Electrocoagulation process using raw sewage for treatment and energy production - Mohd Nasrullah, Zulkifli (2013)
Due to the massive growth of Malaysian population, sewage water has become one of the major water pollution in Malaysia. Various physiochemical and biological technique have been employed to treat sewage water such as aerobic and anaerobic biological treatment, membrane filtration, adsorption, chemical coagulation and many others methods but either they took a long period of time or needed a large amount of chemical substance, both ways are less effective in treating sewage. The removal of pollutants from effluents by electrocoagulation (EC) has become an attractive method in recent years. This electrochemical process offer some distinctive advantages, including effects due to the production of polyvalent cations from the oxidation of corrodible anodes (like Fe2+ and Al3+) as a coagulant agent and the production of electrolysis gases. The gas bubbles can carry the pollutant to the top of the solution where it can be more easily collected and removed. Therefore, EC process has been studied to treat sewage water and to determine the effect of various operating parameters such as electrode types, operating time, current intensity, inter-electrode spacing and pH to evaluate the possible treatment efficiency. It was found that the application of high current intensity (20 A, 25A and 30 A) is more effective in treating sewage than using low current (1 A, 2A and 3 A). Aluminum hydroxypolymeric species formed during an earlier stage of the operation efficiently remove sewage molecules by precipitation, and in a subsequent stage, Al(OH)3 flocs trap colloidal precipitates and make solid−liquid separation easier during the flotation stage. A Response Surface Method (RSM) showed that the optimum condition of COD, BOD and SS removal was obtained 29.09 A of current, 29.86 minutes of operating time, 10.71 mm of inter-electrode distance and pH value of 7.04. Light microscopy result shows more aggregation of sewage particles occurs with longer treatment period and higher current applied to the EC system. High production of hydrogen gas obtained from experiment in 60 seconds by high current application. The study is important to establish a sustainable clean energy in order to implement low cost treatment in sewage treatment.